2022
DOI: 10.31501/rbcm.v30i1.13418
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Da Distribuição Da Carga Interna De Treinamento No Desempenho De Salto Vertical Em Uma Pré-Temporada De Jogadores De Voleibol De Elite

Abstract: O objetivo deste estudo foi examinar os efeitos da distribuição da carga interna de treinamento no desempenho de salto vertical durante a pré-temporada em jogadores de voleibol. A amostra foi composta por 11 jogadores de voleibol da Superliga Masculina de Voleibol (26,4±5,7 anos; 96,6±9,0 kg; 197,6±7,8 cm; 8,1±2,8% de gordura). A pré-temporada foi composta por 11 semanas de treinamento, dividida em três etapas: Etapa 1 (E1), com duração de 6 semanas; Etapa 2 (E2), com duração de 3 semanas; Etapa 3 (E3), com du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Data were predominantly collected during preparatory and competitive periods (50%) ( Andrade et al, 2021 ; Brandão et al, 2018 ; Debien et al, 2018 ; Duarte et al, 2019 ; Horta et al, 2020 ; Mendes et al, 2018 ; Timoteo et al, 2021 ). Three studies collected RPE-based data during the preparatory period only (21%) ( Berriel et al, 2022 ; Domingos et al, 2022 ; Horta et al, 2019 ), and other three during the competitive period only (21%) ( Clemente et al, 2020 ; Lima et al, 2020 ; Ungureanu et al, 2021 ). One study reported data during the transition period between clubs and national team camps (7%) ( Rabbani et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data were predominantly collected during preparatory and competitive periods (50%) ( Andrade et al, 2021 ; Brandão et al, 2018 ; Debien et al, 2018 ; Duarte et al, 2019 ; Horta et al, 2020 ; Mendes et al, 2018 ; Timoteo et al, 2021 ). Three studies collected RPE-based data during the preparatory period only (21%) ( Berriel et al, 2022 ; Domingos et al, 2022 ; Horta et al, 2019 ), and other three during the competitive period only (21%) ( Clemente et al, 2020 ; Lima et al, 2020 ; Ungureanu et al, 2021 ). One study reported data during the transition period between clubs and national team camps (7%) ( Rabbani et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…All included studies used the BORG-CR10 scale to calculate the sRPE ( Table 3 ). “How was your training session?” was the most used question (29%) ( Andrade et al, 2021 ; Brandão et al, 2018 ; Domingos et al, 2022 ; Duarte et al, 2019 ), followed by “how was your workout?” (21%) ( Debien et al, 2018 ; Horta et al, 2019 ; Ungureanu et al, 2021 ). Four studies (29%) did not report the question that was used ( Berriel et al, 2022 ; Mendes et al, 2018 ; Rabbani et al, 2021 ; Timoteo et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations